348. Characterization of 41Ar production in air at a PET cyclotron facility. (December 2018) - Cicoria, G.; Cesarini, F.; Zagni, F.; Pancaldi, D.; Vichi, S.; Marengo, M.
Abstract : Purpose: 41 Ar (t1/2 = 109.34 m) is produced by the activation of air due to the neutron flux during production of PET nuclides in a medical cyclotron facility, according to the 40 Ar(n, γ) 41 Ar reaction. We describe a relatively inexpensive and readily reproducible methodology of air sampling used for quantification of 41 Ar during routine production of PET nuclides. Methods: The activity concentration of 41 Ar was evaluated during the routine production of 18 F − performed using a GE PETtrace Cyclotron. Irradiations were performed at (53–60) μA of current on a Niobium body, high pressure target, filled with 2.5 mL of 99% enriched 18 O water. We realized an air sampling system that allows collecting representative air samples during an irradiation within the cyclotron bunker, in the ducts of the ventilation system, just before final filtering and before emission to external atmosphere. The air sampling system is composed by polyethylene tube, fitted to a Marinelli beaker (total filling volume 1.41 dm 3 ) and to an air pump; the flow rate was set to 2 dm 3 /min. For all samples, at the end of the irradiation, each Marinelli beakers was brought to the gamma ray spectrometry laboratory; the beaker was measured using an HPGe detector. In order to assess the Total Effective Dose (TED) to the population living in the area surrounding the facility, the data on the total amount of 41 Ar released were input in the code HotSpot. Results: A total of 39 samples collected in 4 different conditions were used and analyzed; in particular: inside the cyclotron bunker with ventilation off, inside the cyclotron bunker with ventilation on, in the extraction air duct before and after the final filter. For all samples, the only radionuclide identified was 41 Ar. The average 41 Ar saturation yield per one litre of air emitted in the environment, after the final filter, resulted to be (0.044 ± 0.007) Bq/(μA·dm 3 ). The maximum value of TED for the critical group of the population resulted less than 0.19 μSv/year. Conclusions: Based on the experimental evidence, the emission of 41 Ar in a busy PET cyclotron Centre is not radiologically relevant (typically assumed as 10 μSv/year).